2017
DOI: 10.7840/kics.2017.42.2.471
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Techniques and Applications of Text Analytics

Abstract: The demand and interest in big data analytics are increasing rapidly. The concepts around big data include not only existing structured data, but also various kinds of unstructured data such as text, images, videos, and logs.Among the various types of unstructured data, text data have gained particular attention because it is the most representative method to describe and deliver information. Text analysis is generally performed in the following order: document collection, parsing and filtering, structuring, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Word Cloud is an analysis technique that visualizes the number of keywords based on frequency analysis [13]. The method is the were specifically chosen because this allowed for a significant distinction.…”
Section: Discussionmentioning
confidence: 99%
“…Word Cloud is an analysis technique that visualizes the number of keywords based on frequency analysis [13]. The method is the were specifically chosen because this allowed for a significant distinction.…”
Section: Discussionmentioning
confidence: 99%
“…35 It also calculates the probability of each document and word being included in a specific topic and that of each word obtained from the entire document being included in a specific topic. 36 In other words, topic modeling analysis assumes that each article is a collection of arbitrary issues and probabilistically presents the importance of issues and words comprising each article. 37 In this study, core issues were identified in the collected abstracts and labeled, and changes in issues over time were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Setting a proper number of topics is critical, as the results of topic modeling can vary according to the number of previously set topics and proper methods for searching the number of topics studied. 36 Based on a study reporting that a proper number of topics depend on good categorization as determined by researchers, 38 several topics were determined to be well-categorized from the replication analysis in this study. Consequently, using topic modeling by applying the Gibbs sampling method for the LDA analysis, 39 five topics were extracted in this study, with the topic modeling parameters set as α = 0.1 and β = 0.01 according to Zhao et al 39 The search period for 2019 and the abstracts of articles published until February 2019 were excluded from this study, as these could have affected the trend in topics.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reveal that articles on online media and the sharing economy receive high citations, whereas recently published articles on specific topics such as rural tourism and ecotourism are frequently cited. This study contributes significantly to the hospitality and tourism literature by examining the impact of topic structure and originality, identified through text mining, on citation counts [28].…”
Section: Previous Research On Maritime Autonomous Surface Ships and B...mentioning
confidence: 99%
“…A network in co-occurrence network analysis comprises nodes and connections (links) between nodes, with each node representing a keyword and each link representing a relationship between keywords. To visually represent the relationship between keywords, each keyword is represented by a dot, and the link between keywords is represented by a line, and the thickness of the line varies depending on how often the two keywords are used together [38]. If a network analysis is conducted for all keywords, it becomes difficult to grasp the meaning due to too many nodes and connections, hence the range of nodes to be included in the analysis must be determined [39].…”
Section: Co-occurrence Analysismentioning
confidence: 99%